Iron metabolism mediates the relationship between Vitamin C and hepatic steatosis and fibrosis in NAFLD - Hu, Zhengyu; Li, Yan; Ma, Bingwei; Lei, Saifei; Wang, Xingchun (Frontiers in Nutrition, 2022)
Vitamin C (Vit C) and iron metabolism are closely related to metabolic disorders. However, the relation between iron storage protein ferritin and Vit C has not been elucidated. We aimed to investigate the crosstalk between Vit C and ferritin and its implications on non-alcoholic fatty liver disease (NAFLD). Clinical information of 3,614 subjects was obtained from the NHANES Public Data 2017–2018. FibroScan data, which estimates liver steatosis and fibrosis and Vit C, were selected to assess factors influencing NAFLD in this cross-sectional study. Ferritin and Vit C among different categories of liver steatosis and fibrosis were assessed by CAP and E value. Logistic regression and RCS models were used to analyze the correlations. In vitro study in hepG2 were conducted to validate the regulations. Ferritin increased while Vit C decreased with more severe hepatic steatosis and hepatic fibrosis (all P < 0.001). Logistic regression models indicated that increased serum ferritin was a risk factor for NAFLD while increased Vit C was a protective factor for NAFLD and hepatic fibrosis after adjusting the continuous and categorical variables. Vitamin C was negatively associated with ferritin. Further mediation analysis identified that ferritin mediates the impact of Vit C on NAFLD (P < 0.05) and cirrhosis (P < 0.001). The experiments on cellular level suggested Vit C alleviated PA/OA induced steatosis and maintains iron homeostasis through inhibiting PA/OA induced upregulation of iron bound protein ferritin and labile iron pool (LIP) induction in hepG2 cells. In conclusion, Vit C was a protective factor, whereas ferritin was a risk factor for hepatic steatosis and fibrosis. Vitamin C alleviated NAFLD and maintained iron homeostasis via ferritin suppression and LIP induction.